Oxford new syllabus mathematics 2 - Ban Har, Yeap (Karachi: Oxford University Press., 2024)
Oxford New Syllabus Mathematics 2 builds on the foundational concepts introduced in the previous book, advancing students' understanding of key mathematical topics such as algebra, geometry, trigonometry, statistics, and probability. The textbook combines theoretical explanations with practical applications, helping students develop problem-solving and critical thinking skills. Each chapter includes worked examples, exercises, and real-world applications to deepen comprehension. Designed to guide students through more complex mathematical concepts, this book provides a solid platform for further mathematical studies, fostering both analytical thinking and practical application in preparation for higher-level mathematics.